Indoor autonomous robot navigation by using visually grounded semantic instructions - Tan, Mei Yu (Nanyang Technological University, 2022)
Navigation is becoming an increasingly substantial part of autonomy in robotics. As the capability of robots is continually researched and developed towards increasing complex tasks, navigation has become a topic that many are diving into. There has been numerous developments in navigation, from using Simultaneous Localization and Mapping to build maps in navigation, to exploring other forms of maps like Topological, Semantics and even Abstract maps. This project will work towards exploring a different kind of navigation that is essentially map-less. This is especially useful in foreign environments that the robot have no knowledge on whatsoever.